TSPAN18 facilitates bone metastasis of prostate cancer by protecting STIM1 from TRIM32-mediated ubiquitination - Qianghua Zhou; Xu Chen; Kai Yao; Yangjie Zhang; Haixia He; Hao Huang; Hao Chen; Shengmeng Peng; Ming Huang; Liang Cheng; Qiang Zhang; Ruihui Xie; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Bone metastasis is a principal cause of mortality in patients with prostate cancer (PCa). Increasing evidence indicates that high expression of stromal interaction molecule 1 (STIM1)-mediated store-operated calcium entry (SOCE) significantly activates the calcium (Ca2+) signaling pathway and is involved in multiple steps of bone metastasis in PCa. However, the regulatory mechanism and target therapy of STIM1 is poorly defined. Methods Liquid chromatography-mass spectrometry analysis was performed to identify tetraspanin 18 (TSPAN18) as a binding protein of STIM1. Co-IP assay was carried out to explore the mechanism by which TSPAN18 inhibits STIM1 degradation. The biological function of TSPAN18 in bone metastasis of PCa was further investigated in vitro and in vivo models. Result We identified that STIM1 directly interacted with TSPAN18, and TSPAN18 competitively inhibited E3 ligase tripartite motif containing 32 (TRIM32)-mediated STIM1 ubiquitination and degradation, leading to increasing STIM1 protein stability. Furthermore, TSPAN18 significantly stimulated Ca2+ influx in an STIM1-dependent manner, and then markedly accelerated PCa cells migration and invasion in vitro and bone metastasis in vivo. Clinically, overexpression of TSPAN18 was positively associated with STIM1 protein expression, bone metastasis and poor prognosis in PCa. Conclusion Taken together, this work discovers a novel STIM1 regulative mechanism that TSPAN18 protects STIM1 from TRIM32-mediated ubiquitination, and enhances bone metastasis of PCa by activating the STIM1-Ca2+ signaling axis, suggesting that TSPAN18 may be an attractive therapeutic target for blocking bone metastasis in PCa.